2015
DOI: 10.1016/j.apjtm.2015.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of propofol on generation of inflammatory mediator of monocytes

Abstract: The propofol can inhibit the expression of TLR-4 and NF-κB to inhibit the activation of p38 and the expression of pro-inflammatory cytokines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…LPS stimulation can induce HMGB1 release from mouse macrophages, however, propofol can inhibit this process leading to downregulation of HMGB1 mRNA and also block the activation of nuclear transcription factor-κB (NF-κB) [ 10 ]. In addition, the propofol can inhibit the expression of toll-like receptor 4 (TLR-4) and NF-κB to block the activation of p38 mitogen-activated protein kinase and the expression of pro-inflammatory cytokines [ 4 ]. However, the actions of propofol to regulate the expressions of interleukin-6 (IL-6), 8 (IL-8) and TNF-α and the correlation with HMGB1 in LPS-stimulated murine macrophage are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…LPS stimulation can induce HMGB1 release from mouse macrophages, however, propofol can inhibit this process leading to downregulation of HMGB1 mRNA and also block the activation of nuclear transcription factor-κB (NF-κB) [ 10 ]. In addition, the propofol can inhibit the expression of toll-like receptor 4 (TLR-4) and NF-κB to block the activation of p38 mitogen-activated protein kinase and the expression of pro-inflammatory cytokines [ 4 ]. However, the actions of propofol to regulate the expressions of interleukin-6 (IL-6), 8 (IL-8) and TNF-α and the correlation with HMGB1 in LPS-stimulated murine macrophage are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of p38 MAPK signaling induces the expression of pro-inflammatory mediators, including COX-2 and tumor necrosis factor-α (TNF-α) [ 20 21 22 ]. Measurement of p38 phosphorylation levels in the blood monocytes of mice with endotoxemia revealed that LPS can induce p38 phosphorylation; propofol treatment could significantly inhibit p38 phosphorylation, indicating that propofol has an anti-inflammatory effect [ 8 ]. Furthermore, propofol was shown to inhibit p38 MAPK phosphorylation in alveolar epithelial cells and cardiomyocytes [ 20 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Propofol is an intravenous anesthetic commonly used for general anesthesia and sedation owing to its rapid onset of action and short recovery time [ 8 ]. In recent studies, propofol has been shown to have anti-inflammatory effects in vitro as well as in vivo .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few decades, several researchers have reported its protective effects in ischemic-reperfusion injury, including cerebral ischemic injury. Most of these reports attributed propofol's neuroprotective effect to its anti-inflammatory (Nie et al, 2015 ; Samir et al, 2015 ) and antioxidant (Ucar et al, 2015 ; Hsiao et al, 2016 ) properties. However, in the clinical setting, propofol is often administered to patients with an intact central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%